Major, trace and platinum-group element geochemistry of the Upper Triassic nonmarine hot shales in the Ordos basin, Central China. (February 2015) - Qiu, Xinwei; Liu, Chiyang; Mao, Guangzhou; Deng, Yu; Wang, Feifei; Wang, Jianqiang
Highlights: The Upper Triassic Chang 7 hot shales developed under anoxic environment. Humid paleoclimate was favorable for the deposition of the Chang 7 hot shales. Tectonics is the major control on the development of the Chang 7 hot shales. Abstract: The Upper Triassic Chang 7 non-marine hot shales have been proven to contribute to Mesozoic oil reservoirs in the Ordos basin, Central China. These shales have been studied extensively in sedimentology, petrology and organic geochemistry. However, the factors controlling the development of the shales are still ambiguously constrained. This paper presents the major, trace, and platinum-group elements (PGEs) data to address these issues. The Chemical Index of Alteration (CIA), Chemical Index of Weathering (CIW), C -values and clay mineral compositions indicate that the Chang 7 hot shales were developed in a humid paleoclimate. The indicators of redox conditions (Eu/Eu ∗, Ce/Ce ∗, Ceanom, δU, U/Th, V/(V + Ni) and V/Cr) suggest that the Chang 7 hot shales were developed under anoxic environment. Uranium enrichment (average 46.10 ppm) is an important distinguished signature of the Chang 7 hot shales, which was mainly related to synchronous volcanic ash sediments and/or possibly hydrothermal fluids. The PGE concentrations of the Chang 7 hot shales were reported for the first time here, and can be subdivided into two groups. The total abundances of the Group One samples are relatively lower and derived mainly from detrital minerals, while the Group Two samples are relatively higher, and are also likely linked to the synchronous volcanic ash sediments and/or possibly hydrothermal fluids. Combined with the regional geological setting, we tentatively propose that the tectonics is the major control on the development of the Chang 7 hot shales.